Molecular characterization of Chickpea chlorotic dwarf virus strain D in Chickpea (Cicer arietinum) from District Dera Ismail Khan Khyber Pakhtunkhwa, Pakistan - Rashid, Kamran; Nahid, Nazia; Ramzan, Faiqah; Khan, Muhammad Asaf; Shaheen, Shabnum; Nasim, Ammara; Masood, Nazish; Briddon, Rob W; Hussain, Khadim (Cellular and Molecular Biology, 2019)
Chickpea chlorotic dwarf virus (CpCDV), a member of genus Mastrevirus (family Geminiviridae) is an important viral pathogen of chickpea and other legume crops in Middle East, North Africa, India and Pakistan. Among sixteen known strains of CpCDV three are known to infect legume crops in Punjab province of Pakistan. In this study diversity of CpCDV was explored in Khyber Pakhtunkhwa (KP) province of Pakistan. In year 2016, during a survey in the chickpea growing areas of district Dera Ismail Khan, CpCDV infected plants were identified. Leaf samples were collected, and a diagnostic PCR confirmed mastreivrus infection in 4 out of 100 samples. From these samples full-length genome of CpCDV was amplified using specific back-to-back primers. Virus molecules were sequenced to their entirety and sequence analysis of a molecule KRF4 (GenBank accession # KY952837) showed the highest pair wise sequence identity of 97% with a CpCDV molecule (KM229787) isolated from chickpea plant. An SDT analysis revealed it to be the D strain of CpCDV and a recombination detection program (RDP) showed it to be a recombinant between C (KM229780) and L (KT634301) strains of CpCDV. Thus, further supporting the intra-species recombination for CpCDV and presence of the same strain in chickpea growing areas of Pakistan other than Punjab province. This is the first identification of CpCDV (genus Mastrevirus family Geminiviridae) from chickpea (Cicer arietinum) plants in District Dera Ismail Khan, KP province, Pakistan.